Adenovirus-mediated Expression of a Truncated PDGFβ Receptor Inhibits Thrombosis and Neointima Formation in an Avian Arterial Injury Model - Ding, Hongliu; Wang, Rongqing; Marcel, Robin; Fisher, Daniel Z. (Thrombosis and Haemostasis, 2001)
Platelet-derived growth factor (PDGF) is a major mediator of neointima formation after arterial injury. We constructed a recombinant adenovirus, Ad/PDGFtr, that expresses the soluble extracellular domain of the murine PDGFβ receptor (PDGFtr). The expressed PDGFtr was appropriately glycosylated and secreted by chicken vascular smooth muscle cells (SMCs) in vitro. The expressed PDGFtr inhibited human PDGF-BB induced receptor autophosphorylation, and also inhibited PDGF-BB induced cell proliferation without affecting PDGF-AA induced mitogenesis. In vivo transduction of balloon-injured rooster femoral arteries with Ad/PDGFtr resulted in expression and secretion of the glycosylated PDGFtr. The expressed PDGFtr significantly inhibited neointima formation compared with controls. Neointima-associated thrombus was significantly reduced in Ad/PDGFtr transduced arteries compared with controls. Thus, in addition to impacting on SMC proliferation and migration, PDGF-BB plays a role in thrombus formation in response to arterial injury. Growth factor inhibition by localized gene delivery constitutes a powerful approach to intervene in the molecular pathways involved in vascular disease.
Keywords: Platelet-derived growth factor; mitogenesis; thrombosis; angioplasty